Palaeolatitudinal gradients along the southeastern Palaeo-Pacific margin and the distribution of Early Jurassic bivalves - Damborenea, Susana Ester (2015)
Presence-absence bivalve species data for each Early Jurassic stage along southeastern South America between 20 and 46°S present-day latitude were processed by a set of analytical methods to analyse the palaeolatitudinal patterns of diversity and distribution. The expected decrease in species diversity towards higher latitudes is punctuated by a consistent local diversity increase between 34 and 42°, especially evident during Pliensbachian and Toarcian times, which may be due to an abrupt change in palaeogeography at that latitude, coinciding with the Curicó direct connection to the open ocean and the establishment of an increased variety of habitats within the extensive Neuquén Basin. The proportions of systematic groups show relative increases towards both higher latitudes (Crassatelloidea, Nuculanoidea, Pectinoidea, Monotoidea, Inoceramoidea) and lower latitudes (Trigonioidea, Pholadomyoidea, Limoidea, Lucinoidea). Epifaunal bivalves were dominant during the Hettangian but by Pliensbachian–Toarcian times they were less common than infaunal ones, while semi-infaunal species had low diversities during the whole Early Jurassic. This study suggests that (a) large scale geographical conditions should be taken into account for the analysis of latitudinal diversity trends among benthonic faunas; and (b) latitudinal trends of some living bivalve lineages may have a longer and more complex history than previously thought.